Progress in lung and colorectal cancer survival, in Cyprus (2004-2017): a population-based study. (20th October 2021) - Quattrocchi, A; Demetriou, CA; Cory, OA; Saad, B; Constantinou, C; Papamichael, D; Charalambous, H; Demetriou, A; Scoutellas, V; Kolokotroni, O
Abstract: Background: Lung and colorectal cancer are the leading causes of cancer deaths in Cyprus. We describe preliminary analysis of (overall and by stage of diagnosis) age-standardised 5-year net survival (hereafter reported as NS) trends, for these two cancers. Methods: We analysed data from the national population-based Cyprus Cancer Registry on adults (age 15+) diagnosed between 2004-17 with lung or colorectal cancer with follow-up until December 2019. We used cohort approach for 2004-08 (time 1-T1), 2009-13 (T2) and period approach for 2014-17 (T3) to estimate NS and 95% confidence interval (CI). Stage at diagnosis was categorised as localised, regional and distant, based on the Surveillance Epidemiology and End Results. The International Cancer Survival Standard age-specific weights were used for standardisation. Results: Between 2004-17, all-stages NS increased from 16% (CI:15-17; T1) to 22% (CI:21-23; T3) and from 57% (CI:56-59; T1) to 61% (CI:60-62; T3) for lung and colorectal cancer, respectively. For lung cancer, NS increased from 37% (CI:29-47; T1) to 55% (CI:47-65; T2) and 65% (CI:57-74; T3) for diagnosis at localised stage, from 28% (CI:23-35; T1 and CI:22-35; T2) to 39% (CI:33-46; T3) for regional stage and from 4% (CI:3-6; T1) to 6% (CI:4-8; T2) and 7% (CI:6-10; T3) for distant stage. For colorectal cancer, NS increased from 75% (CI:71-80; T1) to 76% (CI:72-79; T2) and 84% (CI:80-87; T3) for diagnosis at localised stage, from 65% (CI:62-68; T1) to 69% (CI:66-72; T2) and 72% (CI:69-74; T3) for regional stage and from 11% (CI:9-16; T1) to 12% (CI:9-16; T2) and 15% (CI:12-19; T3) for distant stage. Conclusions: Over the study period, survival improvements were observed. Late stage at diagnosis seems to be a contributing factor to decreased survival of lung or colorectal cancer patients in Cyprus. Increasing public awareness of cancer risk factors and symptoms and investment in early detection is vital to reduce delay in diagnosis and treatment and to improve survival. Key messages: Lung and Colorectal cancer survival continues to improve although at different pace by stage at diagnosis. Any shift to earlier stages at diagnosis brings substantial survival improvements. Survival trends can help both in the formulation of strategies for cancer prevention, screening, and treatment and in the assessment of their effectiveness.